VERTICAL CHANGES OF RECENT OSTRACODE ASSEMBLAGES AND ENVIRONMENT IN THE INNER PART OF JAKARTA BAY, INDONESIA - Lili Fauzielly; Toshiaki Irizuki; Yoshikazu Sampei (JOURNAL OF COASTAL DEVELOPMENT, 2012)
A short sediment core from the inner part of Jakarta Bay, Indonesia, was quantitatively analysed for ostracods (minute Crustacea), total organic carbon (TOC) and total nitrogen (TN) contents, and the vertical distributions were recorded. A total of 53 ostracod species were obtained from 80 continuous core samples. The dominant species were Keijella carriei and Loxoconcha wrighti, which are common in areas with high TOC and TN contents. Based on an analysis of ostracod assemblages and carbon/nitrogen ratio, the study site began to be influenced by organic contamination from around 1950. Although the population of Jakarta City has increased rapidly since then, TOC and TN contents which were low, have gradually increased (0.7%–0.9% and 0.10%–0.12%, respectively), probably due to addition of nutrients from river sedimentation. The increased sedimentation rate after 1950 resulted in an increasing TOC ratio. The observed correlation between TOC and dominant species shows that Phlyctenophora orientalis may be a good indicator for monitoring increases in the narrow TOC content range of 0.7%–1.1%.